PENGARUH TERAPI ASSERTIVE TRAINING TERHADAP INTERAKSI SOSIAL SISWA DALAM BERKOMUNIKASI MELALUI BIMBINGAN KELOMPOK DI SMK HASANAH PEKANBARU - Romanda Sari; Elni Yakub; Roby Maiva Putra (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to examine the effect of assertive training therapy on students' social interactions in communicating at Pekanbaru Hasanah Vocational School. This type of research is a quantitative study with an experimental method using the One-Group Pretest-Posttest Design research design. The measuring instrument used in this study is the scale of measurement of social interaction of students in communication consisting of 53 items before the validity, and after the validity obtained 29 valid items with validity of 0.396 and reliability of 0.812 The subjects of this study were 7 students of Pekanbaru Hasanah Vocational School who were identified as having low levels of social interaction in communication. The data analysis technique used is non-parametric statistical techniques using the Wilcoxon test. The results of the study proved that the research hypothesis was accepted. To that end, it can be concluded that there are differences in scores of students' social interactions in communicating before and after being given treatment in the form of assertive training. From the results of Rank Spearman test obtained r = 0.778 while the correlation coefficient r2 is 0.605. Thus there is the effect of assertive training therapy on social interaction of students in communication by 60,5% in Pekanbaru Hasanah Vocational School.Key Words: assertive training, student social interaction in communication